Cerebral achromatopsia: colour blindness despite wavelength processing. - Cowey, A; Heywood, C (1997)
Cortical colour blindness is caused by brain damage to the ventro-medial occipital and temporal lobes. A possible explanation is that the pathway responsible for transmitting information about wavelength and its subsequent elaboration as colour has been destroyed at the cortical level. However, several signs of chromatic processing persist in an achromatopsic subject who, despite his inability to tell colours apart, can still detect chromatic borders, perceive shape from colour, and discriminate the direction in which a striped pattern moves when the determination of direction requires the viewer to 'know' which stripes have a particular colour. Perhaps only the information about wavelength that leads to conscious awareness of colour has been destroyed. It is unclear whether incomplete achromatopsia is merely a less severe form of the disorder or whether it is qualitatively different, perhaps reflecting impaired colour constancy. In monkeys, removing cortical area V4 impairs performance on colour constancy tasks but, invariably, impairs several other aspects of visual perception. If the lesion that causes total achromatopsia in human subjects corresponds to area V4 in monkeys, it is an unsolved puzzle that a totally achromatopsic subject paradoxically demonstrates certain characteristics of colour constancy, unless his residual performance reflects the much underrated retinal contribution to colour constancy.